Tony Redmond's Microsoft Exchange server 2003 with SPI - Redmond, Tony, 1959- (Amsterdam ; Boston : Elsevier/Digital Press, 2005)
With over 40% new and revised material throughout the book, this updated version provides thorough coverage of implementation, migration and management issues for Exchange 2000 and 2003, all backed up by best practices developed by HP, Microsofts only world-wide Prime Integrator for Exchange. The best and most comprehensive coverage of Exchange from the Chief Technology Officer of HP Services, Microsofts only worldwide Prime Integrator for Windows and Exchange. - With over 40% new and revised material throughout the book, this updated version provides thorough coverage of implementation, migration and management issues for Exchange 2000 and 2003, all backed up by best practices developed by HP, Microsoft's only world-wide Prime Integrator for Exchange. - New coverage of Exchange Intelligent Message Filter - Revised and updated coverage of best practices for the design, deployment, and operation of Exchange 2003 - Comprehensive treatment of major issues facing email deployments, including anti-virus and anti-spam techniques - Review of Microsoft's future strategy for Exchange since dropping the Kodiak approach.
A brief history of Exchange -- Exchange and the active directory -- Exchange basics -- Outlook : the client -- Outlook web access -- Internet and other clients -- The store -- Performance and clusters -- Getting the mail through : routing and message delivery -- Managing Exchange : users -- Managing Exchange : servers.
Includes bibliographical references and index.
Keywords: Microsoft Exchange server; Client/server computing; Electronic books